Ecologia de flebotomíneos (Diptera, psychodidae) e sua interação com leishmania (Kinetoplastida, trypanosomatidade) e hospedeiros vertebrados em áreas de transmissão de leishimanioses - Silva, Antonia Suely Guimarães e (2016)
The Sandflies are insects diptera nematocera belonging to the Psychodidae family, very important for public health, because some species are vectors of etiological agents of leishmaniasis, endemic parasitic disease in the state of Maranhão and in Brazil. These vectors are frequently found in natural ecotopes, domestic animal shelters and human habitations. This research aimed to study the occurrence of sandflies in the urban and rural peridomiciliary environment of municipality of Caxias, Maranhão, in notification area of cases of cutaneous and visceral leishmaniasis, as well as the rate of natural infection by Leishmania and analysis of blood food source. This is a cross-sectional, exploratory, descriptive and field study, with a quantitative approach, performed from March 2013 to February 2015. The specimens were collected with CDC (Center for Disease Control) light traps type in 20 homes, 10 in urban area and 10 in rural area. Were collected 15,895 specimens belonging to 17 species, one of genus Brumptomyia and 16 of Lutzomyia. The most abundant species were Lu. longipalpis (90.26%) and Lu. whitmani (7.65%). In the urban area the abundance of sandflies was higher in rainy season, and in the rural area in the dry season. Lu. longipalpis and Lu. whitmani occurred in two seasons, most frequently in rainy and dry season, respectively. From a total of 3, 520 female, 982 samples were used for DNA and PCR-RFLP extraction for detecting the presence of Leishmania. The vector Lu. longipalpis was found infected by Le. infantum (3.0%); Le. shawi (0.3%); Le. mexicana (0.2%); Le. braziliensis (0.6%) and Le. guyanensis (0.6%) and with mixed infection Le. infantum/Le. braziliensis (0.6%). The specie Lu. whitmani was infected by Le. infantum/Le. braziliensis (4.0%) and Le. braziliensis (4.3%). Other species found infected include: Lu. trinidadensis with Le. infantum/Le. braziliensis and Lu. evandroi and Lu. termitophila with Le. braziliensis and Le. guyanensis respectively. Based on these results it is suggested adopting control measures by the public health authorities to contain a future epidemic of AVL in this area, which is also endemic to ACL. For detection of food source were captured 778 engorged females, 573 were positive for eight different types of domestic and wild animals: dog, man, chicken, ox, pig, horse, rodent and opossum; obtaining mixed reactions in eight different associations: dog/rodent, man/chicken, chicken/rodent, dog/chicken, horse/rodent, rodent/pig and man/opossum. The presence of sandflies species infected with different species of leishmanias and fed with blood of domestic animals and human justifies the occurrence of endemic form of visceral and cutaneous leishmaniasis in the municipality of Caxias. Based on these results it is suggested adoption of control measures by the public health authorities to contain a future epidemic of these diseases.